A Study of the Processes of Natural Resources and Community Organization culture Management in Ubonratchathani Province - Tabaselo, Phrabaidega Supot (Journal of International Buddhist Studies, 2023)
The objectives of this research were to study the participatory management process and procedure in natural resource conservation and environment management in relation to community organization culture in Ubonratchathani Province.The process used was qualitative research by studying three target groups in the Province including Mae Moon Man Yuen group, Hua Hew village, Tambon Khongchiam, Khongchiam district and the other two community forest conservation groups at Koo Khad village, TambonNonglao and Tahlad village, Tambon Koh-ae, Khueangnai district. Data were collected from the three groups by the methods of nonparticipatory observation and informal interview with fifteen laymen and monks who were selected from the members of each group. The research findings revealed that the process of local community organization culture management included the participation in community work, attachment of an ideology, working plan, giving an opportunity for expression, having common vision, and transferring and exchanging work experiences. The aspects of participation were the exchange of views and learning from experiences with various groups together with collaboratively seeking the ways of coping with problems through a right understanding of ecological system. The developmental approaches of community organization culture were teamwork, creativity, enhancement of members’ capacity and efficiency of organization administration, learning and opening for other applicable organization culture and behavioral reinforcement which will sustainably help solve the problems of natural resources and environmental management in the long run.